ANALISIS PERSIAPAN DAN PEMANFAATAN SIMRS DI RS BALIMBINGAN KABUPATEN SIMALUNGUN - Batu Bara, Muhammad Hanafi; Lewis, Andreas (Jurnal Inovasi Kesehatan Masyarakat, 2024)
The generation and processing of SIMRS is a responsibility of every hospital. Improvements in operational reporting, decision-making speed, problem-identification accuracy and speed, strategy formulation ease in managerial implementation, work culture, transparency, unit coordination, system understanding, and cost reduction administration are all necessary for the successful processing and development of SIMRS to enhance and support hospital health service processes. There has been no integration between the Balimbingan Hospital's SIMRS processing and the financial and administration department from 2018 to 2021. In light of these issues, it is critical to examine the challenges encountered by Balimbingan Hospital in 2021 while implementing the Hospital Management Information System in Simalungun Regency, North Sumatra Province. This study employs a descriptive model with a System of Action unit of analysis and is qualitative in nature. It takes the form of a case study. Presented findings from an investigation of the implementation and utilization of SIMRS at Balimbingan Hospital in Simalungun Regency through the use of participant observation and in-depth interviews. People who are familiar with the issues under investigation and can provide insight into the current state of affairs are called "informants" in this study. The analysis and discussion led to the conclusion that the Balimbingan Hospital SIMRS is an application of a hospital service management system. The implementation of this system has full support from management and all employees. The goal is to help the hospital improve its services by integrating the entire flow of service processes. The only section that needs to be done manually is the Finance and Management section, but other than that, everything else is done using the system. Additionally, in the event of issues with the internet network, particular measures can be taken, such as establishing a secondary network via a more reliable cable or wireless technology, or establishing a modem connection to the server as a backup, and designating specific IT officers to deal with SIMRS issues.